Analisis Celebrity Endorsment, Persepsi Harga Dan Electronic Word Of Mouth Terhadap Minat Beli Pada Aplikasi Shopee - Mutiara Sandesta; Budi Istiyanto (ITB AAS INDONESIA Surakarta, 2022)
The convenience that consumers get while purchasing products or services through Shopee app has to consider many factors, so any company involved in the sale will always pay attention to these different factors, hoping that consumers will be interested or take advantage of them. The purposeaof this study was to analyze the effect of celebrity endorsements, price perception, and electronicaword of mouth on purchase interest in the Shopee app. This research uses hypothesis testing, which assesses the accuracy of the proposed hypothesis and is tested using statistical tests. The samplingatechnique used in this study is targeted sampling. The data analysis techniqueaused multiple linear analysis.The test is calculated using SPSS 26.0 for Windows. Data processing consists of validity and reliability testing, normality testing, descriptive analysis, calculation of the coefficient of determination, and simultaneous (FTest) and partial (TTest) performance of hypothesis tests. This result is available for 100 respondents, whereby the results of the variables celebrity, price perception and electronic word of mouth have a positive effect on the purchase interest of partial and simultaneous calculations. The effect is 73.9% on the purchase interest. Keywords: Celebrity Endorsment, Price Perception, Electronic Word Of Mouth, Buying Interest